Scaphoid Fracture Patterns—Part Two: Reproducibility and Demographics of a Simplified Scaphoid Fracture Classification - Drijkoningen, Tessa; Mohamadi, Amin; van Leeuwen, Wouter F.; Schwarcz, Yonatan; Ring, David; Buijze, Geert A. (Journal of Wrist Surgery, 2019)
Objective To analyze the reproducibility, reliability, and demographics of a simplified anatomical scaphoid fracture classification based on posteroanterior radiographs using a large database of scaphoid fractures.Methods The study consisted of a retrospective review of electronic medical records of 871 consecutive patients. All patients presented between 2003 and 2014 at two centers. Patient- and surgeon-related factors were analyzed. Additionally, interobserver reliability of the Herbert and simplified scaphoid fracture classifications were tested.Results Proximal pole fractures were defined as fractures in which the center of the fracture line was proximal to the distal scapholunate interval (n = 30), waist fractures (n = 802) were defined as fractures involving the scaphocapitate interval, and distal tubercle fractures (n = 39) were defined as fractures involving the scaphotrapeziotrapezoid (STT) interval. The interobserver reliability of the simplified classification was fair (κ = 0.37) as for the Herbert classification (κ = 0.31). The average doubt of the answers of the observers was 2.1 on a scale from 0 to 10 for the simplified classification and 3.6 for the Herbert classification (P < 0.05).Conclusions All complete fractures across the entire scaphoid distal to the scapholunate articulation and proximal to the STT joint can be classified as waist fractures; nonwaist scaphoid fractures are uncommon (6%) and have somewhat different presentations compared to waist fractures. Simplifying the fracture classification slightly improves interobserver reliability, although remaining fair, and significantly reduces doubt.Level of Evidence This is a Level III, prognostic study.
Keywords: scaphoid fracture; reproducibility; demographics; classification